“...COMING TO COMMON PEACE TOGETHER WITH OUR ALLIES”: ROMANIA’S FOREIGN POLICY BALANCING DURING WORLD WAR I - Ярослав ПОПЕНКО; Ігор СРІБНЯК; Наталя ЯКОВЕНКО; Віктор МАТВІЄНКО (Cхід, 2021)
The article covers the course of negotiations between the plenipotentiaries of Romania and the leading states of the Entente and the Quadruple Alliance during the First World War. Facing the dilemma of determining its own foreign policy orientation – by joining one of the mentioned military-political blocs, the Romanian government was hesitating for a long time to come to a final decision. At the same time, largely due to this balancing process, official Bucharest managed to preserve its sovereign right to work out and make the most important decisions, while consistently defending Romania's national interests. By taking the side of the Entente and receiving comprehensive military assistance from Russia, Romania at the same time faced enormous military and political problems due to military superiority of the allied Austrian and German forces at the Balkan theater of hostilities. Their occupation of much of Romania forced official Bucharest to seek an alternative, making it sign a separate agreement with the Central Block states. At the same time, its ratification was being delayed in every possible way, which enabled Romania to return to the camp of war winners at the right time. At the same time, official Bucharest made the most of the decline and liquidation of imperial institutions in Russia and Austria-Hungary at the final stage of the First World War, incorporating vast frontier territories into the Kingdom. Taking advantage of the revolutionary events in Russia, the Romanian government succeeded, in particular, in resolving the “Bessarabian problem” in its favor. In addition, Romania included Transylvania, Bukovina and part of Banat. An important foreign policy achievement of Romanian diplomacy was signing of the 1918 Bucharest Peace Treaty, as well as its participation in the Paris Peace Conference.